Rancang Bangun Sistem Pendukung Keputusan Inventory Pakaian Adat berbasis Web menggunakan Fuzzy Inference Tsukamoto (Studi Kasus : Toko Bali Antic) - I Made Subiantara Putra; I Gde Putu Wirarama Wedaswhara W.; I Gede Pasek Suta Wijaya (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2021)
Traditional clothing is a symbol of clothing in an area that has an identity and is characterized as a relevant cultural symbol. Inventory control is very important to take into account because shortage or excess inventory is a factor that triggers an increase in costs. In daily operations, the data collection process that is still done manually is mostly done in clothing sales stores, so there are many mistakes from the responsible departments such as sales, the absence of forecasting the need for goods is also a problem for the efficiency of store operational costs. This research was developed in line with the problems that are often faced at the Bali Antic Shop. Seeing this, a website-based custom clothing inventory decision support system was developed using the Tsukamoto fuzzy method. This system is applied in determining the percentage of sales with input variables of price margin, demand and existing inventory. In this research, it is proven by comparison between manual calculation and system calculation, and the result is the percentage of sales.